2016
DOI: 10.1007/s00216-016-9725-3
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the extraction of pharmaceuticals from sewage sludge and soil: an experimental design approach

Abstract: Pharmaceuticals can enter the environment when organic waste products are recycled on agricultural soils. The extraction of pharmaceuticals is a challenging step in their analysis. The very different extraction conditions proposed in the literature make the choice of the right method for multi-residue analysis difficult. This study aimed at evaluating, with experimental design methodology, the influence of the nature, pH and composition of the extraction medium on the extraction recovery of 14 pharmaceuticals,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 36 publications
(91 reference statements)
3
21
0
Order By: Relevance
“…Similarly, Lee et al also determined the LOQs as ten times the S/N ratio, and obtained a LOQ for sulfamethazine that was equal to ours (0.5 ng g −1 ), but the one for sulfamethoxazole was lower (0.5 vs. 2.5 ng g −1 ) [33]. Finally, Ferhi et al determined the LOQs with the results of the validation data in a more similar way to ours for diclofenac, sulfamethoxazole, and sulfamethoxazole, our values being lower in the first two cases and slightly higher but in the same range in the latter (2.1 ng g −1 vs. 5 ng g −1 ) [34].…”
Section: In House Validation Studiessupporting
confidence: 68%
“…Similarly, Lee et al also determined the LOQs as ten times the S/N ratio, and obtained a LOQ for sulfamethazine that was equal to ours (0.5 ng g −1 ), but the one for sulfamethoxazole was lower (0.5 vs. 2.5 ng g −1 ) [33]. Finally, Ferhi et al determined the LOQs with the results of the validation data in a more similar way to ours for diclofenac, sulfamethoxazole, and sulfamethoxazole, our values being lower in the first two cases and slightly higher but in the same range in the latter (2.1 ng g −1 vs. 5 ng g −1 ) [34].…”
Section: In House Validation Studiessupporting
confidence: 68%
“…disposal or agricultural application of organic waste products that may contain trace levels of these substances, like manure, wastewater treatment plant effluents, and sewage sludge [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16].…”
mentioning
confidence: 99%
“…According to past studies, mixing organic acids (including formic acid [39], phosphate [41], Na 2 EDTA-Mcllvaine [38,42]) with methanol [37] or ACN [43] is the most effective extraction solution with good recovery efficiency and has good reproducibility when analyzing multiple antibiotic residues in environmental matrices. Ferhi et al [34] demonstrated that ACN and citric acid-phosphate buffer can be used to efficiently extract eight antibiotics from the soil. The increase in ionic strength caused by the addition of Na 2 EDTA increases the solubility of the target compound in the organic solvent (ACN) of the extraction medium, thereby improving the extraction efficiency.…”
Section: Choice Of Extractantmentioning
confidence: 99%
“…One method that solves these problems is the QuECh-ERS method. Past studies have applied it to various food substrates such as radishes [25], milk [26], honey [27], vegetables [28][29] and environmental substrates such as plant tissues [30], manure [31], wastewater [32], sludge [33][34], and sediments [35]. At present, the QuEChERS method has been used to extract antibiotics from the soil matrix and most studies focused on the extraction of a single type of antibiotic or a certain number of antibiotics [36][37].…”
Section: Introductionmentioning
confidence: 99%